Open Surgery with Intraoperative Enteroscopy in Jejunoileal Massive Bleeding in Pediatric Patient: An Evidence-Based Case Report - Husni, Rini Y; Rinaldhy, Kshetra (UI Scholars Hub, 2019)
Introduction. A case report of surgical exploratory laparotomy with intraoperative enteroscopy (IOE) as a treatment in massive jejunoileal bleeding in children. Method. We conducted a literature search on databases such as Cochrane, PubMed, ScienceDirect, and Google Scholar. Abstract and title screening was done based on exclusion criteria, inclusion criteria, and double filtering. The selected article then reviewed using critical appraisal tools based on its validity, importance, and applicability. Selected articles were benchmark to the discussion. Results. The application of open surgery with IOE as the final treatment that can be recommended in the critical or life-threatening condition of jejunoileal bleeding. Conclusion: surgical exploratory laparotomy with intraoperative enteroscopy is the best final treatment that can be a choice for massive jejunoileal bleeding, whether in the acute case or repeated case, supported with the level of evidence 4